Iatrogenic bladder injury: A single institution’s ten-year experience in treatment and outcome 1999-2009, Kuala Lumpur, Malaysia (Colombia Medica, 2011)
Introduction: This case series is a retrospective review of iatrogenic bladder injuries treated at our institution Universiti Kebangsaan Malaysia, Medical Centre, over a ten-year period, from 1999 to 2009. Materials and methods: A retrospective review of the operating theater database yielded the names and registration numbers of patients who underwent operative repair of bladder injuries. Patients who sustained bladder injuries due to non-surgical reasons (such as traumatic bladder injuries due to pelvic fractures, blunt trauma or penetrating injuries to the pelvis) were excluded. Results: There were 12 cases of iatrogenic bladder injury treated during this time. A total of eight injuries occurred during gynaecological surgery. Five injuries occurred during lower segment caesarean section, two injuries during total abdominal hysterectomy and bilateral salpingo-oopherectomy, and a single injury during Burch colposuspension. Four out of the five injuries during caesarian section had a history of previous caesarian section. Of the four remaining non-gynaecological related injuries, two injuries occurred during hernioplasty, one during exploration of an enterocutaneous fistula and the other was during laparoscopic appendicectomy. Conclusion: Iatrogenic bladder injury should be anticipated in patients undergoing caesarean section who have had multiple previous caesarean sections. Iatrogenic injuries should be identified intra-operatively to enable early repair and the best outcome. These injuries were adequately assessed by ascending cystography. Continuous repair with absorbable sutures together with perivesicle drainage and bladder catheterization produces good outcome.